Storage of wood chips : effect of chip size on storage properties - Anerud, Erik (Array, 2020)
To make forest biomass more competitive, increased efficiency in the handling and supply system is needed, thus producing high-quality fuel at a lower cost. Operating costs can be reduced if the target chip size is increased, as this increases productivity and reduces chipper fuel consumption. However, the chips need to be storedin order to meet fluctuating seasonal demand and maintain high machine utilisation. Due to biomass degradation, storage of comminuted biomass can lead to high energy losses, but can also increase fuel quality, e.g. by reducing moisture content and increasing net calorific value. This study evaluated the effects of storage on dry matter losses and differences in fuel quality of the stored biomass for three target chip sizes and three materials during six months of storage. The results showed that coarse chips had significantly lower moisture content and lower energy losses after storage than fine chips. Overall, changes during storage resulted in an economic loss of 3–4% per oven-dry ton for fine chips, but an economic gain of 2–6% for coarse chips. Thus increased target chip size can increase the competitiveness of forest biomass through decreased production costs and reduced storage costs. It can also ensure higher, more consistent fuel quality.